The Sustainable Business Performance in Construction Industry in Brunei Darussalam - Khan, Asghar Ali; Permana, Dudi (Dinasti Publisher, 2025)
This study analyses the influence of Green HR Practices, Green Employee Behaviour, and Management Information Systems on Sustainable Business Performance in the construction industry. The research focuses on human resources within construction companies in Brunei, examining professionals in managerial and supervisory roles. A quantitative approach is employed, utilizing probability sampling techniques and a Likert-scale-based questionnaire to collect data. Structural Equation Modelling (SEM) using Smarts is applied for data analysis. The findings indicate that Green HR Practices have a significant direct influence on Sustainable Business Performance. Green Employee Behaviour demonstrates a moderate influence, while Management Information Systems play a supporting role in enhancing sustainable outcomes. The study emphasizes the critical role of Green HR Practices as a driver for achieving sustainability in the construction sector, highlighting their potential to foster employee engagement and organizational performance.